IoT Based Solar Panel for Power and Current Monitoring - Mohd Zalinanlpazli, Puteri Najwa Aida Elieyana; Mohd Shah, Nor Shahida; Abu Hassan, Omar; Mohd Rafain, Nurul Asyiqin; Ahmad Jahid, Nur Hasya Afiqah (Progress in Engineering Application and Technology, 2023)
The Internet of Things envisions the internet extending into the real world, including common things. The Internet of Things allows things to be sensed or controlled remotely using existing network infrastructure, allowing for full integration of the real world into computer-based systems and resulting in enhanced efficiency, accuracy, and economic gain, as well as less human interaction. This technology has several uses, including solar cities, smart villages, microgrids, and solar street lighting, among others. During that same time frame, renewable energy increased at a quicker rate than at any previous time in history. The suggested system relates to the online display of solar energy power utilization as a renewable energy. Smart Monitoring highlights daily renewable energy use. This assists the user in analyzing energy use. Examine the effects on renewable energy consumption and electrical challenges.